Short- and long-term reproductive effects of prenatal and lactational growth restriction caused by maternal diabetes in male rats - Amorim, Elaine M. P.; Damasceno, Débora Cristina [UNESP]; Perobelli, Juliana E.; Spadotto, Raquel [UNESP]; Fernandez, Carla D. B. [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Kempinas, Wilma D. G. [UNESP] (Biomed Central Ltd., 2011)
Background: A suboptimal intrauterine environment may have a detrimental effect on gonadal development and thereby increases the risk for reproductive disorders and infertility in adult life. Here, we used uncontrolled maternal diabetes as a model to provoke pre- and perinatal growth restriction and evaluate the sexual development of rat male offspring.Methods: Maternal diabetes was induced in the dams through administration of a single i.v. dose of 40 mg/kg streptozotocin, 7 days before mating. Female rats presenting glycemic levels above 200 mg/dL after the induction were selected for the experiment. The male offspring was analyzed at different phases of sexual development, i.e., peripuberty, postpuberty and adulthood.Results: Body weight and blood glucose levels of pups, on the third postnatal day, were lower in the offspring of diabetic dams compared to controls. Maternal diabetes also provoked delayed testicular descent and preputial separation. In the offspring of diabetic dams the weight of reproductive organs at 40, 60 and 90 days-old was lower, as well as sperm reserves and sperm transit time through the epididymis. However the plasma testosterone levels were not different among experimental groups.Conclusions: It is difficult to isolate the effects directly from diabetes and those from IUGR. Although the exposure to hyperglycemic environment during prenatal life and lactation delayed the onset of puberty in male rats, the IUGR, in the studied model, did not influenced the structural organization of the male gonads of the offspring at any point during sexual development. However the decrease in sperm reserves in epididymal cauda and the acceleration in sperm transit time in this portion of epididymis may lead to an impairment of sperm quality and fertility potential in these animals. Additional studies are needed in attempt to investigate the fertility of animals with intrauterine growth restriction by maternal diabetes and possible multigenerational effects.
Keywords: developmental programming; growth restriction; male rat; maternal diabetes; puberty; sexual development